Peran Dan Kedudukan Dewa Dalam Teks Bhagawadgita - Dharmawan, I Gusti Agung (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The Bhagavad Gita is one of the most important sacred texts of Hinduism. It contains profound spiritual teachings, including about the role and status of gods. The difference in the concept of gods in the Vedas and the Bhagavad Gita can be traced back to the difference in the concept of God in the two scriptures. In the Vedas, God is depicted as a transcendent being, who is outside the universe. Whereas in the Bhagavad Gita, God is depicted as an immanent being, who is present within the universe. In the Bhagavad Gita, gods are depicted as powerful and compassionate beings. They are the creators, preservers, and destroyers of the universe. Gods also play a role as spiritual teachers who guide humanity towards enlightenment. This article discusses the role and status of gods in the Bhagavad Gita. It discusses how gods are depicted in the text, and how they play a role in human life. The article aims to discuss the concept of gods in the Vedas, and to find explanations about gods, their role and status in the Bhagavad Gita. Based on the study, the concept of gods in the Vedas is different from the Bhagavad Gita. In the Vedas, gods are often equated with God, whereas in the Bhagavad Gita, gods are different from God. This difference is seen in the 39 verses of the Bhagavad Gita that deal with the role, status, and nature of the gods. This shows that the Bhagavad Gita teaches not only about the role and status of gods, but also about the nature of God itself.